Assessment of autonomic nervous system dysfunction in multiple sclerosis and the association with clinical disability - Nilufer Kale; Setty Magana; Jale Agaoglu; Osman Tanik (MDPI AG, 2009)
Background: Recent studies have reported autonomic dysfunction (AD) in multiple sclerosis (MS), bladder and/or bowel dysfunction, orthostatic hypotension, and cardiac adaptation disorders have been observed in a wide range (15-80%). The primary aim of this study is to investigate the frequency and association of AD in MS patients, assessed by sympathetic skin reaction (SSR) and a symptoms questionnaire. The secondary aims of this study are to study the association of AD and disease disability assessed by expanded disability status scale (EDSS), as well as disease duration. Design and Methods: 100 clinically definite MS patients were evaluated for ANS dysfunction by use of an autonomic symptoms questionnaire and SSR testing. The relationship between these methods, AD and disease-related parameters, such as the expanded disability status scale (EDSS) and disease duration were all evaluated. Results: 65% of the patients presented with AD and 29% of these patients had abnormal SSR results. MS patients with high EDSS values (EDSS >4) and longer disease duration were more likely to have ANS dysfunction (p less than 0.0001). Conclusions. ANS dysfunction is not uncommon in CDMS patients and thus noninvasive investigations of AD are warranted to optimize AD evaluation and disease management.